COMMUNITY EMPOWERMENT THROUGH THE SMALL SCALE BIO-DEGISTER TO ACCOMPLISH CATTLES WASTE IN THE KIDANG VILLAGE - Dwi Pangga; Baiq Muli Harisanti; Lalu Habiburahman; Ahmadi Ahmadi (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2017)
The purpose of this KKN-PPM program is to accomplish a problem from cattles waste that has not been managed properly. Further management is directed towards making small-scale biodegesters into energy-independent villages. This devotion is implemented in Kidang Village of East Praya in Central Lombok Regency. The availability of an abundant source of cattle dung is spread in each private cowshed (there is no collective cowshed) because of the distribution pattern of Kidang Village residents in small groups, supporting the implementation of this program. The soil texture of cracked clay in the dry season, as well as the limitations of the water source cause the degister model are suitable for the condition. Degister applied is a small-scale biodegister, designated for 1 family with the number of cattle at least 2 cattles (cow). Biodigester is installed in 6 different location as a pilot program to Kidang Village community. Digester uses a 1200 liter plastic tank, with in let, out let, and out putt gas using a piping system. The digester is filled with Â¾ part of the cattle dung, and Â¼ of the part as the gas reservoir. The gas produced from the digester model shows a mixture of water : cattle dung with a 2: 1 ratio is faster than the 1: 1 mixture. In the mixture with a ratio of 2: 1, the gas has begun formed on day 11 with increasing pressures day by day, with the pressures of 73.26 Pa, 106.36 Pa, and 112.00 Pa.